EQUITY IN HOUSING: EXAMINING THE EFFECTIVENESS OF URBAN RENT LAWS - Singh, Gurpal (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Despite growing debate about the efficacy of urban rent laws in promoting housing equity, however, the issue of affordability is critical in cities that are expanding quickly. These laws are meant to set limits on the prices of rent, prevent unfair evictions of renters, and secure access to affordable housing, especially for low and middle income families. Proponents say such laws can blunt the effects of escalating rents and housing instability, but critics warn they could result in market distortions, disincentives for new housing construction, or diminished property upkeep. In this paper I move beyond the simple dichotomy of making or breaking markets to encapsulate the multifaceted children of urban rent laws, in cities with a housing crisis, that foster equitable access to housing. Additionally, it assesses the performance of different rent control and stabilization models that have been implemented around the world, assessing their ability to produce long term housing affordability and equity. It also looks at unintended effects:The housing market by outsiders, the curtailment of some investments in housing quality, and the possibility of discriminatory effects in rental practices. In this thesis, I use analysis of case studies, empirical data, and a ’thought experiment’ to test this hypothesis and to assess to what extent urban rent laws can balance affordable housing with the dynamics of urban producing real estate, from which one may draw conclusions about the viability of urban rent laws as a sustainable approach to housing inequality in contemporary cities.